2020
DOI: 10.1186/s43055-020-00273-4
|View full text |Cite
|
Sign up to set email alerts
|

B-mode ultrasound, color Doppler, and sonoelastography in differentiation between benign and malignant cervical lymph nodes with special emphasis on sonoelastography

Abstract: Background Enlarged cervical lymph nodes are the most commonly encountered neck lumps. Ultrasonography is the most extensively used tool for classification of superficial lymph nodes due to its availability and low cost. Ultrasound (US) elastography refers to a non-invasive imaging technique that can describe tissue displacement (i.e., strain) or stiffness in response to a given force. The aim of this study is to compare between B-mode sonography, color Doppler, and sonoelastogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…In our study, lymph nodal echogenicity had a diagnostic accuracy of 67%. Similar results were obtained in a study by Abdelgawad et al [ 8 ]. Benign lymph nodes (tuberculous and reactive lymphadenitis) tend to have homogenously hypoechoic echo pattern.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, lymph nodal echogenicity had a diagnostic accuracy of 67%. Similar results were obtained in a study by Abdelgawad et al [ 8 ]. Benign lymph nodes (tuberculous and reactive lymphadenitis) tend to have homogenously hypoechoic echo pattern.…”
Section: Discussionsupporting
confidence: 92%
“…Benign lymph nodes (tuberculous and reactive lymphadenitis) tend to have homogenously hypoechoic echo pattern. However, lymphomatous and metastatic cervical lymph nodes can also be hypoechoic [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar accurate results of sensitivity were also declared by Tan et al, Teng et al, and Abdelgawad et al, and they are 98.1, 96.4, and 92.8%, respectively. 8 16 17 In contradictory, Lo et al reported low sensitivity of 66.7% regarding elastography, and Acu et al observed sensitivity of 82.1%. 11 18 Both studies finally concluded that elastography has no additional benefits over B-mode and color Doppler ultrasound to improve the differentiation between malignant and benign nodes.…”
Section: Discussionmentioning
confidence: 99%
“…16,23 Abdelgawad et al also documented that one out of two patients with TB lymphadenitis was misdiagnosed as a malignant lesion by sonoelastography. 17 The false diagnosis is mainly based on the presence of internal calcification due to long-term organization that causes increased elasticity and may mimic malignancies. 23 Six patients were encountered as false-positive results in our study, one of them was TB lymphadenitis and the other five had nonspecific lymphadenitis of long duration more than 8 weeks before diagnosis that also led to increased fibrous tissue in internal structures and consequently appeared hard in consistency.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is versatile masquerader as it can resemble infection or neoplasm and poses a diagnostic challenge to the clinicians 9 and on ultrasound and elastography. 10 B-mode sonography-Tubercular lymph nodes are large, S/L ratio>0.5, shows absence of echogenic hilum, intranodal necrosis, calci cation. Similar observations were made by Park J H et al 11 Ying et al 12 in their study including 315 tuberculous nodes, reported that 79% had increased S/L ratio >0.5 however the percentage was less than that in metastatic nodes 95%.…”
Section: Discussionmentioning
confidence: 99%